Participatory and responsive governance in universal health coverage: an analysis of legislative provisions in Thailand. Issue 2 (18th February 2021) - Marshall, Aniqa Islam; Kantamaturapoj, Kanang; Kiewnin, Kamonwan; Chotchoungchatchai, Somtanuek; Patcharanarumol, Walaiporn; Tangcharoensathien, Viroj
Abstract : Participatory and responsive governance in universal health coverage (UHC) systems synergistically ensure the needs of citizens are protected and met. In Thailand, UHC constitutes of three public insurance schemes: Civil Servant Medical Benefit Scheme, Social Health Insurance and Universal Coverage Scheme. Each scheme is governed through individual laws. This study aimed to identify, analyse and compare the legislative provisions related to participatory and responsive governance within the three public health insurance schemes and draw lessons that can be useful for other low-income and middle-income countries in their legislative process for UHC. The legislative provisions in each policy document were analysed using a conceptual framework derived from key literature. The results found that overall the UHC legislative provisions promote citizen representation and involvement in UHC governance, implementation and management, support citizens' ability to voice concerns and improve UHC, protect citizens' access to information as well as ensure access to and provision of quality care. Participatory governance is legislated in 33 sections, of which 23 are in the Universal Coverage Scheme, 4 in the Social Health Insurance and none in the Civil Servant Medical Benefit Scheme. Responsive governance is legislated in 24 sections, of which 18 are in the Universal Coverage Scheme, 2 in the Social Health Insurance and 4 in the Civil Servant Medical Benefit Scheme. Therefore, while several legislative provisions on both participatory and responsive governance exist in the Thai UHC, not all schemes equally bolster citizen participation and government responsiveness. In addition, as legislations are merely enabling factors, adequate implementation capacity and commitment to the legislative provisions are equally important.